A Novel, Modular Robot for Educational Robotics Developed Using Action Research Evaluated on Technology Acceptance Model - Avraam Chatzopoulos; Michail Kalogiannakis; Stamatis Papadakis; Michail Papoutsidakis (MDPI AG, 2022)
This research evaluates a novel, modular, open-source, and low-cost educational robotic platform in Educational Robotics and STEM Education. It is the sequel of an action research cycle on which the development of this robot is based. The impetus for the need to develop this came from the evaluation of qualitative and quantitative research data collected during an educational robotics event with significant participation of students in Athens, which showed an intense interest in students in participating in educational robotics activities, but-at the same time-recorded their low involvement due to the high cost of educational robots and robotic platforms. Based on the research's findings, this robot was designed to suit the whole educational community; its specifications came from its members' needs and the processing and analysis of qualitative and quantitative data. This paper presents an evaluation of the robot using the Technology Acceptance Model. The robot was exposed to 116 undergraduate students attending a pedagogical university department to evaluate its handling according to the model's factors. Research results were promising and showed a high degree of acceptance of the robot by these students and future teachers, providing the impetus for further research.